The Role of Macrophages in Staphylococcus aureus Infection - Pidwill, Grace R.; Gibson, Josie F.; Cole, Joby; Renshaw, Stephen A.; Foster, Simon J. (Frontiers in Immunology, 2021)
Staphylococcus aureus is a member of the human commensal microflora that exists, apparently benignly, at multiple sites on the host. However, as an opportunist pathogen it can also cause a range of serious diseases. This requires an ability to circumvent the innate immune system to establish an infection. Professional phagocytes, primarily macrophages and neutrophils, are key innate immune cells which interact with S. aureus, acting as gatekeepers to contain and resolve infection. Recent studies have highlighted the important roles of macrophages during S. aureus infections, using a wide array of killing mechanisms. In defence, S. aureus has evolved multiple strategies to survive within, manipulate and escape from macrophages, allowing them to not only subvert but also exploit this key element of our immune system. Macrophage-S. aureus interactions are multifaceted and have direct roles in infection outcome. In depth understanding of these host-pathogen interactions may be useful for future therapeutic developments. This review examines macrophage interactions with S. aureus throughout all stages of infection, with special emphasis on mechanisms that determine infection outcome.